The Approach of the Holy Qur’an in Formulating Structures that Indicate the Legal Ruling and Its Impact on Interpretation - Aseery, Dalal Ali Jabeer; Bouziane, Meriem Attia (Journal of Islamic and Religious Studies, 2022)
The study deals with the Holy Qur’an’s approach to the formulation of words and structures indicative of the legal ruling and its impact on the exegetical approach. The application of this topic has five verses in the imperative form, four in the form of the prohibition, and five in the predicate form. In addition, a final section consists of verses received in different forms. As for the formulation of structures, it touched upon the internal presumptions affecting the formulation of the text of the legal ruling, represented in the presumptions of the near text, and the inner presumptions of the distant text. It also dealt with the external evidence in the formulation of the text of the ruling, which are represented in the presumption of reasons for revelation, the presumption of speech, the presumption of statement in the Sunnah, and the presumption of abrogation, with an indication of the effect of this on interpretation.